AN IMPROVED ZCZVT-PWM DC-DC BOOST CONVERTER - Sahin, Yakup; Aksoy, Ismail; Ting, Naim Suleyman (YILDIZ TECHNICAL UNIV, 2015)
In this paper, an improved active snubber cell for ZCZVT PWM DC-DC converter is proposed. The improved snubber cell provides zero-voltage transition (ZVT) turn on and zero-current transition (ZCT) turn of for main switch. The snubber decreases EMI noise and operates with soft switching in a wide range of input line and load voltages. Besides, all of the semiconductor devices in the converter operate with soft switching. There is no additional voltage and current stres on the main devices. The improved snubber cell has a low cost and simple structure. The theoretical analysis of converter is clarified and the operating stages is given in detail. Both simulation results and experimental results of converter are obtained by prototype of 500 W and 100 kHz. It is observed that the results are suitable with each other perfectly.
Keywords: ZVT; ZCT; DC-DC converters; soft switching; Engineering